PERENCANAAN KAPASITAS PEMBANGKIT PLTM SUNGAI LOGUNG KARANGTALUN KABUPATEN TEMANGGUNG - Nugroho, Agung (Diponegoro University, 2013)
Central Java Province intends to improve the use of renewable energy (EBT) such as water resources. Logung river at Ngaliyan subdistrict, Temanggung district has potential energy for micro power plan. The first step to use the water resource is determining the capacity of a mini hydro power plan in accordance with the conditions of the river Logung. Based on the the technical study, the elvation height between the prospective weir with potential power house is 110 m and the effetive height at 105 m. Logung maximum river flow is 11.06 m3/dt, with average flow is 4,77 m3/dt., The minimum flow is 0,75 m3/dt. This electricity power is 10253.12 KW with maximum flow, it will be produced 4848.44 KW at maximum flow 60 %. The minimum flow can deliver 695,28 KW. The suitable capacity for the generator of micro power plants of Logung is 3220 KVA when it is according to manufacture. Key words : power, flow, power